The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1007/s12663-011-0231-z
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Standard of Operative Notes within an Oral and Maxillofacial Surgery Department, using an Operative Note Proforma

Abstract: Previous papers have discussed various methods of improving operative note standards. We present statistical evidence for the use of an Operative Note Proforma to improve operative note standards within Oral and Maxillofacial Surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 5 publications
1
17
0
Order By: Relevance
“…They form an important part of patients case notes and hence the must be complete and legible. 5 Several previous studies have assessed the quality of operative notes, and all these studies, in their initial assessment have found that neither RCSE guidelines nor the respective sub-speciality association guidelines were fully followed properly. [5][6][7] This is similar to what we found after our initial audit and served as the reason for implementing a change in our practice.…”
Section: Discussionmentioning
confidence: 99%
“…They form an important part of patients case notes and hence the must be complete and legible. 5 Several previous studies have assessed the quality of operative notes, and all these studies, in their initial assessment have found that neither RCSE guidelines nor the respective sub-speciality association guidelines were fully followed properly. [5][6][7] This is similar to what we found after our initial audit and served as the reason for implementing a change in our practice.…”
Section: Discussionmentioning
confidence: 99%
“…The orthopaedic proforma used in Sheffield previously highlighted how the addition of these specialty-specific headings improved documentation [7]. Proforma benefits pertaining to operative documentation have been highlighted in other surgical specialties previously [11-12]. Shah, et al have shown statistically significant improvement in orthopaedic operation note documentation when using the British Orthopaedic Association guidelines and the RCS guidelines as a template for their total knee replacement (TKR) and total hip replacement (THR) operation notes [6].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, 20% of the notes had illegible parts, similar to findings in other studies. 10,13 Legibility of signatures can be improved by the use of name stamps.…”
Section: Discussionmentioning
confidence: 99%